Material and Visual Revolutions. Post-production Tools for Change - Simone Fehlinger (Diseña, 2020)
Since contemporary Western visual culture constitutes its reality in images, reality can be post-produced through editing techniques — as artist and writer Hito Steyerl suggested. Departing from this hypothesis, this paper explores post-production as both a conceptual tool as well as a concrete design method and practice in order to change the Anthropocene’s actualities. It illustrates the assembling gesture of post-production as a tool of knowledge creation and presents furthermore the preconditions of a scenario with the capacity to alternate already post-produced contemporary worlds. The ongoing project New Weather TV focuses on the production, diffusion, and reception of the Anthropocene through the image. In considers that, given that the Earth has been transformed into a television studio, a design studio, weather is an everyday screen practice that incorporates modern and Anthropocene ideologies into our daily realities. The project aims to re-design the images of the weather report in order to perform non-colonial and non-Anthropocene attitudes via the technique of chroma keying.